2023
DOI: 10.1101/2023.08.09.552632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative proteomics uncovers low asparagine insertion inPlasmodiumtRip-KO proteins

Martina Pitolli,
Marta Cela,
Delphine Kapps
et al.

Abstract: tRNAs are not only essential for decoding the genetic code, but their abundance also has a strong impact on the rate of protein production, folding, and on the stability of their encoding messenger RNAs. Plasmodium expresses a unique surface protein called tRip, involved in the import of exogenous tRNAs into the parasite. Comparative proteomic analysis of the blood stage of wild-type and tRip-KO variant of P. berghei parasites revealed that down-regulated proteins in the mutant parasite are distinguished by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several observations support the fact that the Plasmodium AIMP tRip, combined to one or both MSCs, is involved in the import of exogenous tRNAs inside the parasite, and that their import could compensate for the deficiency of some Plasmodium tRNAs. The deletion of the gene-encoding tRip not only leads to a reduction in overall protein synthesis, but also to a selective drop in asparagine-rich proteins in the parasite [14,17]. Moreover, the (human) tRNA Asn is one of the favorite binders of (P. falciparum) tRip, which increases its chances of import [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations support the fact that the Plasmodium AIMP tRip, combined to one or both MSCs, is involved in the import of exogenous tRNAs inside the parasite, and that their import could compensate for the deficiency of some Plasmodium tRNAs. The deletion of the gene-encoding tRip not only leads to a reduction in overall protein synthesis, but also to a selective drop in asparagine-rich proteins in the parasite [14,17]. Moreover, the (human) tRNA Asn is one of the favorite binders of (P. falciparum) tRip, which increases its chances of import [43].…”
Section: Discussionmentioning
confidence: 99%
“…In Plasmodium, tRip is an AIMP like no other: it is an integral membrane protein anchored in the plasma membrane of the parasite [13,14]; it homodimerizes using an alternative interface, named 1 ′ [13,15,16]; and it allows the formation of two MSCs characterized by two different GST-like domain organizations [13]. Most importantly, tRip is involved in the import of exogenous (host) tRNAs into the parasite [14] and its deletion leads to low infectivity and translational efficiency, which especially affects asparagine-rich proteins [17]. To date, it has not been demonstrated that Apicomplexa other than Plasmodium import and use host tRNAs.…”
Section: Introductionmentioning
confidence: 99%